The toxicology mechanism of endophytic fungus and swainsonine in locoweed - Wu, Chenchen; Han, Tiesuo; Lu, Hao; Zhao, Baoyu (Environmental toxicology and pharmacology, 2016)
Locoweed is a perennial herbaceous plant included in Astragalus spp. and Oxytropis spp. that contains the toxic indolizidine alkaloid swainsonine. The livestock that consume locoweed can suffer from a type of toxicity called locoism. There are aliphaticnitro compounds, selenium, selenium compounds, and alkaloids in locoweed. The toxic component in locoweed has been identified as swainsonine, an indolizidine alkaloid. Swainsonine inhibits lysosomal a-mannosidase and mannosidase II, resulting in altered oligosaccharide degradation and incomplete glycoprotein processing. Corresponding studies on endophytic fungi producing swainsonine have been isolated from a variety of locoweed, and these endophytic fungi and locoweed have a close relationship. Endophytic fungi can promote the growth of locoweed and increase swainsonine production. As a result, livestock that consume locoweed exhibit several symptoms, including dispirited behavior, staggering gait, chromatopsia, trembling, ataxia, and cellular vacuolar degeneration of most tissues by pathological observation. Locoism results in significant annual economic losses. Therefore, in this paper, we review the current research on locoweed, including that on locoweed species distribution in China, endophyte fungus in locoweed, the toxicology mechanism of locoweed, and the swainsonine effect on reproduction.